2005
DOI: 10.21273/hortsci.40.5.1239
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Variation in Alkamides and Cichoric Acid in Roots and Aboveground Parts of Echinacea purpurea (L.) Moench

Abstract: We investigated patterns of variation in alkamides and cichoric acid accumulation in the roots and aboveground parts of Echinacea purpurea (L.) Moench. These phytochemicals were extracted from fresh plant parts with 60% ethanol and quantified by high performance liquid chromatography (HPLC) analysis. Concentrations of alkamides and cichoric acid were measured on a dry-weight basis (mg·g–1). For total alkamides, concentrations among individual plants varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
3
24
0
2
Order By: Relevance
“…However, the alkamides 8 and 9 content differed significantly in each of the tissues assayed, with roots containing highest levels of alkamides 8 and 9. These results are in agreement with other reports (Wills & Stuart, 1999;Qu et al, 2005;Thygesen et al, 2007). The alkamides 8 and 9 contents were also affected by cultivar.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, the alkamides 8 and 9 content differed significantly in each of the tissues assayed, with roots containing highest levels of alkamides 8 and 9. These results are in agreement with other reports (Wills & Stuart, 1999;Qu et al, 2005;Thygesen et al, 2007). The alkamides 8 and 9 contents were also affected by cultivar.…”
Section: Resultssupporting
confidence: 93%
“…Qu et al (2005) reported that the level of cichoric acid varied considerably between flower heads and roots of E. purpurea. The E. purpurea grown in Slovenia had cichoric acid of 10.76 and 15.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has constantly been one of the best selling genera in the American herb market (Qu et al . ). Because of the high demand for Echinacea , harvest has brought about a swift development of Echinacea cultivation throughout the world (Li ).…”
Section: Introductionmentioning
confidence: 97%
“…pallida. Of these three, E. purpurea is used most frequently, making up about 80% of commercial production (Qu et al 2005).…”
Section: Chapter: Echinacea and Its Modern Medicinal Usesmentioning
confidence: 99%